2010
DOI: 10.1136/hrt.2009.188250
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities as predictors of incident coronary heart disease and cerebrovascular disease

Abstract: In this prospective population-based sample, childhood adversities were associated with a significantly increased risk of objectively verified cardiovascular disease, especially among women but to a lesser extent among men. More studies with prospective settings are needed to confirm the association and possible mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
95
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 47 publications
(31 reference statements)
4
95
1
1
Order By: Relevance
“…11 In Finland, poor psychosocial and socioeconomic circumstances in childhood have been found to be associated with poor heart health as defined by the American Heart Association 2 and with an increased risk of acute ischemic heart or cerebrovascular disease in men. 10 Elsewhere, a 3-fold risk of stroke was found among men who had experienced parental divorce compared CI indicates confidence interval. *Based on log-binomial regression models with generalized estimating equations estimation taking into account the intracluster dependence of individuals residing within the same municipalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In Finland, poor psychosocial and socioeconomic circumstances in childhood have been found to be associated with poor heart health as defined by the American Heart Association 2 and with an increased risk of acute ischemic heart or cerebrovascular disease in men. 10 Elsewhere, a 3-fold risk of stroke was found among men who had experienced parental divorce compared CI indicates confidence interval. *Based on log-binomial regression models with generalized estimating equations estimation taking into account the intracluster dependence of individuals residing within the same municipalities.…”
Section: Discussionmentioning
confidence: 99%
“…10,13 The respondents were asked whether they had experienced the following in their childhood: divorce/separation of the parents, longterm financial difficulties in the family, serious conflicts in the family, frequent fear of a family member, serious or chronic illness of a family member, and alcohol problem of a family member. Response categories for each item were as follows: no=0, yes=1, or "cannot say," which was coded as missing data.…”
Section: Childhood Psychosocial Adversitymentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent large cohort studies have added to this evidence of accumulation of adversities in childhood, with financial difficulties, divorce or bereavements, (which in one study had occurred most commonly in those with lower education levels in adulthood) being associated with increased risk of stroke 53 and overall cardiovascular disease 54 in adulthood even after adjustment for conventional risk factors.…”
Section: Early Life Influencesmentioning
confidence: 99%
“…180 Severe childhood adversities such as physical and sexual abuse are emerging independent risk factors for the incidence of ischemic heart disease among women. 181,182 A recent metaanalysis showed that anxiety is a moderate but independent risk factor for incident ischemic heart disease and cardiac death in both men and women, although individual study results are heterogeneous.…”
Section: Depression and Other Psychosocial Risk Factorsmentioning
confidence: 99%